Divine breath of Genesis (Joyce Mansour). Issue 1 (July 2017) - Elhariry, Yasser
Abstract : In this two-part essay, I present an overview of early to mid-twentieth-century francophone Cairo, followed by a close reading of Joyce Mansour's translingual lyric and prose. In Part One, I situate the history of francophone Cairo's literary communities and vibrant print culture within the broader context of trans-Mediterranean cultural exchanges between Egypt and France. I sketch francophone Cairo's ultimate demise in relation to the contemporaneous Vortex movement in England. In light of this history, I follow in Part Two with a poetic query, situated at the crossroads of the local, the international, and the translingual. I recast the vigour of Vorticist energies through the sociocultural gyre of early twentieth-century Cairo, by focusing first on a brief sociolinguistic moment in the history of Egyptian cinema. This allows me to reveal the curious linguistic and poetic underbelly of the Cairo vortex, which I illustrate by way of a close reading of the city's most iconoclastic poet, Joyce Mansour. Spanning references from Shakespeare to Byron to Dickinson, Mansour's lyric and prose showcase a unique literary translingualism that simultaneously speaks in and between more than one tongue. In contrast to francophone Egypt's prose literature, Mansour's case presents an alternate perspective on the question of language and translation than the one favoured by the dialogue-driven plot narratives of the novel. Within the context of the narratives collected in Histoires nocives, a simple, unassuming translingual pun – construed around the vocal metamorphoses and alphabetical permutations between the vocables oum and mou – points to a more sublimated absence: the narrator's détour to a non-extant ur -language or mother tongue of an obscure, original Genesis or Holy Writ. Mansour writes (in) a composite tongue. Her texts read and sound as if they were not originally written in any one single language in isolation. She adopts a sacred thematization of breaths and a nomadic, translingual poetics, freely halting upon a vast selection of constantly evolving languages and morphing cultural references. As early as 1955, her translingualism provided an exit from monolingual writing practices within international French and francophone literature: the translanguage sustained traces of a foreign linguistic and cultural excess – expended, expunged out of Egypt.